THE ECONOMIC EXPANSION OF THE ANATOLIAN COUNTRYSIDE IN LATE ANTIQUITY: THE COAST VERSUS INLAND REGIONS. - Izdebski, Adam (Late Antique Archaeology, 2013)
This paper examines the archaeological, palynological and textual evidence for economic prosperity in the Anatolian countryside in Late Antiquity. Thanks to the separate analysis of data for coastal and inland regions, it shows that we do not see any substantial differences in the functioning of the rural economy between these two geographical zones. Therefore, the new demand from Constantinople for agricultural produce or a local economy’s proximity to a long-distance exchange network, cannot explain fully the observed phenomena. The vitality and complexity of local economies must also have played an important role in the economic expansion of Anatolia’s late antique countryside.